Intensified Pb(II) adsorption using functionalized KCC‑1 synthesized from rice husk ash in batch and column adsorption studies - Rosalyza, Hasan; Mohd Zaki, Ruhiyuddin; Herma Dina, Setiabudi; Rahimah, Jusoh; Aishah, Abdul Jalil; Shokouhimehr, Mohammadreza (Springer Science and Business Media Deutschland GmbH, 2023)
An attempt to investigate the feasibility of 3-aminopropyltriethoxysilane (3-APTES)-functionalized KCC-1 (NH2/KCC-1) prepared from rice husk ash (RHA) for Pb(II) removal was executed. An effective functionalization of fibrous silica nanospheres (KCC-1) by NH3 was confirmed by FTIR analysis. The optimized condition of Pb(II) adsorption in the batch system was at an initial Pb(II) concentration (X1) of 307 mg/L, adsorbent dosage (X2) of 2.43 g/L, and time (X3) of 114 min, with the Pb(II) removal (Y) of 90.1% (predicted) and 91.2% (actual). NH2/KCC-1 can be regenerated by nitric acid (0.1 M) with insignificant decline of Pb(II) removal percentage (adsorption = 91.2–67.3%, desorption = 77.7–51.9%) during 5 cycles adsorption–desorption study. The examination of column adsorption study at a varying flow rate (1–3 mL/min) and bed height (10–20 cm) showed a good performance at a lower flow rate and higher bed height. Both Adam–Bohalt model and Thomas model displayed a good correlation with experimental data. However, Thomas model was more suitable due to the high correlation coefficient, R2 = 0.91–0.99. This study revealed the intensified Pb(II) adsorption using NH2/KCC-1 synthesized from RHA in batch and column adsorption studies.